IMPROVING STUDENTS’ COMMUNICATIONS SKILLS THROUGH COOPERATIVE LEARNING MODELS TYPE JIGSAW - Marfuah, Marfuah (Universitas Pendidikan Indonesia, 2017)
This study aims to overcome the lack of communication skills of students in social studies activities such as asking and expressing opinions. The study was conducted in Al Qalam Depok Islamic Junior High School in the even semester of the academic year 2015/2016. The method used in this research is Classroom Action Research which refers to the design pattern of Kemmis and Mc. Taggart. The results showed that there was a significant improvement in communication skills after learning in three cycles were performed. In addition, there is an increase in learning outcomes of students. The conclusion of this research is the use of Jigsaw type cooperative learning model can improve the communication skills of learners.